Toba-Bataknese Interjection Ale!: A Natural Semantic Metalanguage Approach - Viqa Sari, Wina; Mulyadi (International Journal Linguistics of Sumatra and Malay, 2024)
Interjections are words used to express emotions or spontaneous reactions. There are various interjections in the Batak Toba language, but the one discussed in this article is the interjection "Ale!". This research aims to understand the meaning of the interjection "Ale!" in the Batak Toba language. The data was collected from the short stories book "Torsa-torsa Ni Halak Batak", a Batak Toba literary work written by Guru Lukas Hutapea. The approach used in this research is Natural Metalinguistic Semantics with a descriptive qualitative method through observation and note-taking. The data was collected by reading and translating the short story book Torsa-torsa Ni Halak Batak and interviewing native speakers of the Batak Toba language. The research results indicate that the interjection Ale! can be categorized into two types of interjections: volitive and emotive. The emotive interjection Ale! expresses feelings of shame, anger, guilt, sadness, dan regret. The volitive interjection Ale! conveys an intention for the conversation partner to perform a specific action. The meanings of the volitive interjection Ale! found include the sentiment of seeking attention, want someone to do something, want someone to know something and want non-human object to do something.